2013
DOI: 10.4236/ajac.2013.412095
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Removal from Rodent Habitat Operations in Space Using Phosphoric Acid Treated Activated Carbon

Abstract: To accommodate long duration biology research with rodent habitats on the International Space Station while providing a healthy living and working environment for crewmembers, NASA Ames Research Center developed a new exhaust filter for odor control for the Animal Enclosure Module (AEM), which houses mice and rats. The new exhaust filter uses activated carbon pellets as adsorbents, with phosphoric acid (H 3 PO 4 ) impregnated on the surface. The deodorization performance of the new exhaust filters for AEM unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This result may be explained by the high BET surface areas of ACs 28 and/or the surface functional groups on the prepared AC samples due to the activation process. 29 The comparison of three AC samples showed that ECAC is the best adsorbent followed by RSAC and then CDAC with a range of investigated ammonia concentrations. ECAC (S BET , 1200 m 2 g À1 ) presents the highest specic surface, while CDAC has the lowest one (700 m 2 g À1 ).…”
Section: Screening Of the Adsorption Performance Of Three Prepared Ac...mentioning
confidence: 94%
“…This result may be explained by the high BET surface areas of ACs 28 and/or the surface functional groups on the prepared AC samples due to the activation process. 29 The comparison of three AC samples showed that ECAC is the best adsorbent followed by RSAC and then CDAC with a range of investigated ammonia concentrations. ECAC (S BET , 1200 m 2 g À1 ) presents the highest specic surface, while CDAC has the lowest one (700 m 2 g À1 ).…”
Section: Screening Of the Adsorption Performance Of Three Prepared Ac...mentioning
confidence: 94%
“…Hence, activated carbon impregnated with H 3 PO 4 (H 3 PO 4 /C) samples were prepared in this study to remedy the drawbacks of H 2 SO 4 /C. Like H 2 SO 4 /C, the spent H 3 PO 4 /C can also be regenerated by flowing low-pressure steam through the adsorbent bed and the regeneration byproduct (NH 4 ) x H 3-x PO 4 [19] can be used as agricultural fertilizer.…”
Section: Introductionmentioning
confidence: 99%